Supervised neural network classifier for voice pathology - Murugesa Pandiyan, Paulraj, Prof. Madya Dr,; Sazali, Yaacob, Prof. Dr.; Sivanandam, S. N.; Hariharan, Muthusamy (Kongu Engineering College, 2011)
Link to publisher's homepage at www.kongu.ac.in/